2006
DOI: 10.1152/ajprenal.00179.2005
|View full text |Cite
|
Sign up to set email alerts
|

Ischemia-induced cleavage of cadherins in NRK cells requires MT1-MMP (MMP-14)

Abstract: Ischemia is a leading cause of acute renal failure (ARF), a disease associated with high morbidity and mortality. Disruption of intercellular adhesion in the proximal tubules is linked to ARF, although the molecular mechanism(s) remains unclear. Our previous studies showed that ischemia is associated with cadherin cleavage and loss in NRK cells, putatively due to a matrix metalloproteinase (MMP) (7). In the current studies, a MMP required for E-cadherin cleavage and N-cadherin loss was identified. Chemical inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
68
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(73 citation statements)
references
References 58 publications
3
68
0
2
Order By: Relevance
“…The inhibition effect of the positive compounds MMP inhibitor II and MMP inhibitor III from Merck were determined with an IC 50 value of 13.05 nM and 10.20 nM, respectively which are consistent with the references 19,20 . For optimal signal to noise ratio, we chose 10 nM cd-MMP-1 and 10 µM of the compound concentration for the initial screening assay.…”
Section: Inhibition Of Cd-mmp-1 By Flavonoidssupporting
confidence: 81%
“…The inhibition effect of the positive compounds MMP inhibitor II and MMP inhibitor III from Merck were determined with an IC 50 value of 13.05 nM and 10.20 nM, respectively which are consistent with the references 19,20 . For optimal signal to noise ratio, we chose 10 nM cd-MMP-1 and 10 µM of the compound concentration for the initial screening assay.…”
Section: Inhibition Of Cd-mmp-1 By Flavonoidssupporting
confidence: 81%
“…31,33,43 In particular, we have shown that increased MMP expression and activity can regulate N-cadherin function through proteolytic degradation. 29,30,44 Cardiac-specific loss of N-cadherin in the heart leads to a dilated cardiomyopathy attributable to loss of the integrity of cell adhesion junctions. 45 Because of their homophilic binding and adhesive specificities, N-cadherin/catenin complex is required for cadherin-mediated cell adhesion and linkage to the actin cytoskeleton.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 Western blot analysis of the myocardial membrane fraction in banded WT and PI3K␣DN mice showed a modest increase in N-cadherin levels ( Figure 6A and 6B), whereas in banded PI3K␥KO mice, there was a 75% loss of N-cadherin levels ( Figure 6A and 6B). In contrast, in the banded PI3K␥KO (and PI3K␣DN) mice, levels of ␤-catenin in the heart were significantly increased compared with banded WT mice ( Figure 6C).…”
Section: Specific Loss Of N-cadherin From Adhesion Complexes While ␤-mentioning
confidence: 99%
“…Cleavage of E-cadherin and shedding of an 80-kD fragment can be mediated by matrilysin, stromelysin-1, 5,6 plasmin 7 and a disintegrin and metalloproteinase 10 (ADAM10). 8 For N-cadherin, a 90-kD fragment can be released by the enzymes matrix metalloproteinase (MMP), 9 plasmin, 10 ADAM10, 11 membrane type 1-MMP (MT1-MMP) 12 and MT5-MMP. 13 Soluble E-cadherin (sE-CAD) has been described in the circulation of cancer patients.…”
mentioning
confidence: 99%